SYSTEMATIC LITERATURES REVIEW ON MARKETING PRICING STRATEGIES - Hussien, Awol (International Journal For Research In Business, Management And Accounting, 2021)
The main purpose of this seminar paper was to reviewed the pricing strategies that have practiced in Business entities (organizations, Industries and farms), why, when and how the development of Appropriate pricing strategies can take place and its effects on desired objectives of Business entities. In reviewing this different researches that were done on the pricing strategies, price setting, the contributing factors and challenges during pricing and development of pricing strategies, examine the methods or approaches used to general pricing, change in price and its strategic decisions, price adjustment strategies and its implication on Business desired objectives were gathered based on secondary data source. Both Search Strategy and Study Selection methods were imployed as a technique of review to identify the existing concepts of pricing process and empirical analysis of pricing strategies based on Systematic Review Approach’s. As many related literatures reviewed on price were thought; as one of the four P’s of the marketing mix, price is one of the most flexible and changed quickly. This helps to understood the necessity of effective pricing, the availability of a number of variables need to be considered when determining a price, challenges and complexity of price, and the effect of mismanagements during pricing process. Additionally, the review was also introduced pricing is an unfamiliar subject for most managers in Marketing and the gap they have as knowledge on pricing process. Therefore, appropriate pricing strategy is considered to be the most critical tools to overcome such challenges and complexity as in the business climate and Managers gaps; in which the first concern must has given to develop a appropriate pricing strategy for the reasons behind direct relationship’s of both price and pricing strategy. Before deciding for selected appropriate pricing strategy in accordance to context of the business entities a serious of attention must has given to all affecting factors when setting a right price, the kind of Approaches and models used to identify pricing strategies and as marketers or managers having knowledge base of theory are a now days paramount concern to overcome challenges in dynamic environments. Since the price has a complex dynamics and quick changing behavior; in similar manner to price company’s/organizations/business must pursue and adopt different price strategies in various markets or situations. Accordingly, when Companies/organizations/business are facing situations where they may need to reduce or increase their prices even after developing their organizations appropriate pricing strategies and structures; the company’s need to be forced for choosing a new appropriated single pricing strategy or integrated pricing strategies that survive with the condition changed. Thus, at the time of this condition has happen, Price Change and Adaptation strategies will be helpful. Finally, based on this review proceeded the author’s implicate for capacitating managers on the knowledge of pricing process and adaptation of innovate pricing strategy by making improvements or adjust that quickly responding to dynamic change in environmental factors.